Bulk and surface recombination properties in thin film semiconductors with different surface treatments from time-resolved photoluminescence measurements - Thomas P. Weiss (Nature Portfolio, 2019)
Abstract The knowledge of minority carrier lifetime of a semiconductor is important for the assessment of its quality and design of electronic devices. Time-resolved photoluminescence (TRPL) measurements offer the possibility to extract effective lifetimes in the nanosecond range. However, it is difficult to discriminate between surface and bulk recombination and consequently the bulk properties of the semiconductor cannot be estimated reliably. Here we present an approach to constrain systematically the bulk and surface recombination parameters in semiconducting layers and reduces to finding the roots of a mathematical function. This method disentangles the bulk and surface recombination based on TRPL decay times of samples with different surface preparations. The technique is exemplarily applied to a CuInSe2 and a back-graded Cu(In,Ga)Se2 compound semiconductor, and upper and lower bounds for the recombination parameters and the mobility are obtained. Sets of calculated parameters are extracted and used as input for simulations of photoluminescence transients, yielding a good match to experimental data and validating the effectiveness of the methodology. A script for the simulation of TRPL transients is provided.